PEMBATALAN SEPIHAK OLEH PEMBELI DALAM SISTEM BAYAR DI TEMPAT MELALUI E-COMMERCE DI BIDANG PESAN MAKANAN ONLINE DI KOTA PEKANBARU - Wigar Johan Hezekia; Firdaus Firdaus; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
E-Commerce is an online buying and selling transactionvia the internet. E-commerce can be accessed through a website orthrough an application. And the various payment methods offered,can be via account transfer, via electronic money and also with theCash on Delivery (COD) payment system. In its implementation,buying and selling transactions online creates problems. Theproblem that occurs is the unilateral cancellation made by the buyerto the merchants so that the merchants suffers a loss. The purpose ofwriting this thesis: First, to find out the arrangements for unilateralcancellation by the buyer in the on-site payment system via e-commerce in the field of online food ordering in the city ofPekanbaru according to the Civil Code. Second, what are theefforts so as not to harm business actors for unilateral cancellationsby buyers in the on-site payment system via e-commerce in the fieldof online food ordering in the city of Pekanbaru.This type of research used in legal research is sociologicallegal research. Where, this research takes an approach by lookingat legal facts and facts in a society in the city of Pekanbaru. Analysisof the data used is the author to analyze data qualitatively.The research results show that unilateral cancellationsmade by buyers cause losses to business actors. This is because themerchants has carried out his obligations but he does not receivepayment. According to the Civil Code, merchants can file a lawsuitagainst buyers who cancel unilaterally. However, the business actordid not file a lawsuit against the buyer. But merchants submitcompensation to e-commerce.Keywords: Unilateral Cancellation – E-Commerce – Cash On Delivery